Pembacaan Heuristik Dan Hermeneutik Untuk Menggali Makna Lagu Pretender Karya Hige Dandism (Kajian Semiotika Riffaterre): Heuristic and Hermeneutic Reading to Explore the Meaning of the Song Pretender by Hige Dandism (Riffaterre's Semiotic Study) - Erika Selphie Damayanti; Mintarsih; Sopaheluwakan, Yovinza Bethvine (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
The song titled Pretender with Japanese verse caused multiple interpretations from various blogs and videos. With the implied meaning of "pretend" in songs, this study aims to analyze and describe the meaning of songs through heuristic and hermeneutic reading. The theory used refers to the semiotics model of Michael Riffaterre. In this study, the method used is a qualitative-descriptive, non-interactive research approach, listening-notes, and literature studies. Based on the results and discussion, heuristic and hermeneutic readings can explore the meaning of the song Pretender by HIGE DANdism, in the form of fear and inferiority of the character I in the song that causes despair that leads to surrender. The meaning of pretending in a song corresponds to its literal meaning, which is to pretend showing something that is inversely proportional to what is felt, or hide the true feeling.